Penerapan Media Gambar Berseri Berbantuan Teknik Montase Pada Pembelajaran Keterampilan Menulis Narasi Siswa Kelas V Sekolah Dasar - Windari, Tutut (South Sulawesi Education Development, 2025)
This research aims to determine the ability of narrative writing skills through serial image media assisted by montage techniques. This type of research is classroom action research which consists of two cycles. Data analysis techniques were carried out descriptively, quantitatively and qualitatively. The subjects of this research were teachers and students of class V at SDN 5 Salamae, Palopo City. Based on the research results, it was found that the increase in writing skills in the pre-cycle was 47.30%, the results of learning to write narratives using serial image media assisted by montage techniques showed an increase from an average value of 65.96% in cycle I to 76.38% in cycle II. . Based on these results, serial image media assisted by montage techniques is recommended for learning narrative writing skills in elementary schools.